Daydream believers - Kaplan, Fred M (John Wiley & Sons, 2008)
Includes bibliographical references (p. 221-230) and index; 6 parts: The mirage of instant Victory; the fog of moral clarity; chasing silber bullets; breaking the world anew; the dreams dissolve into nightmares; waking up to reality; Quỹ Châu Á